Preparation of Co and Ni doped ZnO nanoparticles served as encouraging nano-catalytic application. (10th January 2020) - Ali, M; Sharif, S; Anjum, S; Imran, M; Ikram, M; Naz, M; Ali, S
Abstract: Nickel (Ni) and cobalt (Co) doped ZnO nanoparticles were prepared using simple and cost-effective sol-gel technique. Effects of various weight ratios (5, 10, 15 and 20) % of Co and Ni-doped into ZnO have been examined. The prepared undoped and doped nanoparticles (NPs) were characterized using XRD, SEM, FTIR, EDX and UV-Vis spectroscopy. By analyzing the catalysis potential of the samples under UV irradiation, the probable mechanism of particles was investigated. XRD results revealed that ZnO and doped ZnO have hexagonal wurtzite phase, the lattice strain and particle size were measured by Williamson and Hall plot. The absorption increased and band gap energy decreased gradually in the range of 2.40–3.62 eV upon doping was identified using UV-Vis spectroscopy. The elemental composition of Zn, Ni and O were confirmed with EDX spectra and FTIR spectra demonstrate the presence of chemical bonding and functional groups at the interface of ZnO. This report highlights the effect of nanocatalyst on the degradation rate of methylene blue through NaBH4, results revealed that doped nanocatalyst has better catalytic action than ZnO and will provide an insight for the synthesis of catalytic agents that could prevent environment pollution issue.